Exploring the Opinions of Irish Beef Farmers Regarding Dairy Beef Integration - Maher, James W.; Clarke, AnneMarie; Byrne, Andrew William; Doyle, Rob; Blake, Martin; Cromie, Andrew; Barrett, Damien (Frontiers in Veterinary Science, 2021)
Background There has been very little previous research in Ireland on the opinions of farmers regarding dairy beef integration. The need for increased dairy beef integration has assumed a greater importance in Ireland in recent years due to a rapid expansion in dairy production, and associated increase in numbers of male dairy calves born on Irish farms. The objective of this study was to explore beef farmers’ views on a broad range of issues related to dairy beef integration, using a survey methodology. The survey was distributed to approximately 4,250 beef farmers via email and 1,203 participated in the study. Results The sample was composed almost entirely of beef farmers, although a very small proportion also had a dairy enterprise on their farm. 80% of the farmers were concerned with the increase in the number of male dairy calves in recent years. 57% of farmers responded that they were not willing to rear dairy bred calves for beef. Limousin, Aberdeen Angus and Hereford were the breeds farmers would be most willing to rear for beef. Good health, breed, and conformation were ranked as the main factors calf rearers consider when buying calves. Expectation of poor profit margin, expectation of poor-quality calves, and price volatility/market uncertainty were the top ranked factors dissuading farmers from rearing dairy calves for beef. The main themes arising from the qualitative question related to beef price/ability to make a profit, breed, and calf quality. Conclusions While it is concerning that the majority of respondents expressed an unwillingness to rear dairy bred calves for beef, approximately a quarter of beef farmers indicated a willingness to rear beef-sired dairy calves for beef. In the qualitative responses, farmers described how their concerns about calf quality and their ability to make a profit from dairy bred calves would make it difficult for them to rear these calves for beef. Future strategy will have to consider how these challenges can be overcome and the issues of who bears the risks and costs associated with greater integration will have to be carefully considered.